High expression of CPNE3 predicts adverse prognosis in acute myeloid leukemia. Issue 9 (20th August 2017) - Fu, Lin; Fu, Huaping; Qiao, Jianlin; Pang, Yifan; Xu, Keman; Zhou, Lei; Wu, Qingyun; Li, Zhenyu; Ke, Xiaoyan; Xu, Kailin; Shi, Jinlong
Abstract : CPNE3, a member of a Ca 2+ ‐dependent phospholipid‐binding protein family, was identified as a ligand of ERBB2 and has a more general role in carcinogenesis. Here, we identified the prognostic significance of CPNE3 expression in acute myeloid leukemia (AML) patients based on two datasets. In the first microarray dataset ( n = 272), compared to low CPNE3 expression ( CPNE3 low ), high CPNE3 expression ( CPNE3 high ) was associated with adverse overall survival (OS, P < 0.001) and event‐free survival (EFS, P < 0.001). In the second independent group of AML patients (TCGA dataset, n = 179), CPNE3 high was also associated with adverse OS and EFS (OS, P = 0.01; EFS, P = 0.036). Notably, among CPNE3 high patients, those received allogenic hematopoietic cell transplantation (HCT) had longer OS and EFS than those with chemotherapy alone (allogeneic HCT, n = 40 vs chemotherapy, n = 46), but treatment modules played an insignificant role in the survival of CPNE3 low patients (allogeneic HCT, n = 32 vs chemotherapy, n = 54). These results indicated that CPNE3 high is an independent, adverse prognostic factor in AML and might guide treatment decisions towards allogeneic HCT. To understand its inherent mechanisms, we investigated genome‐wide gene/microRNA expression signatures and cell signaling pathways associated with CPNE3 expression. In conclusion, CPNE3 high is an adverse prognostic biomarker for AML. Its effect may be attributed to the distinctive genome‐wide gene/microRNA expression and related cell signaling pathways. Abstract : High expression of CPNE3 predicts adverse prognosis in acute myeloid leukemia High expression of CPNE3 is associated with distinctive gene/microRNAs expression signatures in acute myeloid leukemia.